Optimization of Business Opportunities Using Google Trends for Students - Wahyudi, Ade; Riskarini, Dian; Trirahayu, Dewi; Irawan, Indra Ade; Setiarini, Setiarini; Sitepu, Refaldi Bremana; Salsabila, Sarah Aini (Golden Ratio of Community Services and Dedication, 2025)
This community service program aimed to enhance entrepreneurial literacy among Generation Z students by optimizing business opportunities through the use of Google Trends. Conducted at SMA Bintara 1 Depok, the activity involved 30 students from grade 11 and was carried out through a descriptive and participatory approach. The methodology included a combination of pre-test, lecture-based training, interactive discussions, post-test, and satisfaction surveys. Data were analyzed descriptively to measure improvements in students’ knowledge. Results showed a significant increase in understanding, with pre-test scores at 6.1% and 3% for Google Trends knowledge and usage respectively, rising to 97% and 93.9% after the intervention. The training successfully introduced students to the practical application of digital tools for market research and business strategy development. The program proved effective in fostering critical thinking, creativity, and systematic decision-making, thus contributing to the preparation of digitally competent young entrepreneurs for the evolving market landscape.